Use of Hemodynamic Ramp Study to Optimize Continuous-Flow Ventricular Assist Device in a Fontan Patient. Issue 5 (July 2019) - Chau, Peter; Lim, Heang M.; Schumacher, Kurt R.; Grifka, Ronald G.; Peng, David M.
Abstract : The utility of hemodynamic ramp studies in single ventricle patients supported by continuous flow left ventricular assist devices (CF-LVADs) is largely unknown. We report the novel use of the hemodynamic ramp test to optimize a 26 year-old Fontan-palliated single-ventricle patient supported with a continuous-flow ventricular assist device (Heartware HVAD). Modest improvements in Fontan hemodynamics resulted in significant and persistent clinical improvement and symptomatic relief.